The relations between parents’ acceptance/rejection and undergraduate adjustment to college: the moderating role of undergraduate collectivism - Niu, Hua; Liu, Jie; Duan, Wenji; Li, Shuna (Frontiers in Psychology, 2024)
IntroductionThe present study examined the moderating effects of undergraduate collectivism in the relations between parents’ acceptance/rejection and undergraduate adjustment to college in Chinese societies.MethodsA survey was conducted covering 5,444 Chinese undergraduates and involved the use of the Parental Acceptance and Rejection Questionnaires (PARQ-short form), the College Student Adaptability Inventory (CSAI), and the Individualism-Collectivism Scale (ICS).ResultsFindings revealed that undergraduate’s collectivism moderated the relations between acceptance/rejection and undergraduate adjustment to college for fathers, but not for mothers. Compared to low collectivism undergraduates, those undergraduates high in collectivism experienced stronger positive impacts from fathers’ acceptance and more pronounced negative effects from fathers’ rejection.DiscussionFindings from this study highlight the importance of considering how the cultural value (such as collectivism) may influence the relation between parenting and child development.